Análisis de las intervenciones terapéuticas en maloclusiones causadas por extracciones prematuras de dientes temporales. - Barrionuevo Marín, Alessia del Carmen (2025)
The purpose of the present investigation was ton analyze the possible therapeutic interventions used in the treatment of malocclusions caused by premature extractions of primary teeth. Therefore, the study is of a bibliographic and descriptive documentary nature, non-experimental and cross-sectional,based on articles published in the last 10 years, using databases sushi as Google Scholar,Pubmed and ProQuest. Seventeen arricles were obtained by means of the PRISMA methodology (Preferred Reposting Items for Systematic Reviews year Meta Analyses), since it is widely accepted worldwide for different scientific publications. As a result, several therapeutic interventions applied by different authors such as space maintainers, space recuperadores, funtional appliances and pediatric prostheses were obtained, highlighting their importance in the management of diverse skeletal and dental variations. Finally, it is concluded that the different interventions are effective in the preservation of the dental arch perimeter, favoring esthetics and correct planning and cooperation. However, effectiveness depends on clinical criteria, early diagnosis and a great commitment on the part of the patient, being thus determinant to evaluate risks, benefits and limitation of each device.